APLIKASI PEMETAAN PONDOK PESANTREN BERBASIS WEB DI KABUPATEN JOMBANG - Baharudin, Ilham; Sujatmiko, Bambang; Faizah, Arbiati (Inovate, 2020)
Jombang Regency is known by the nickname of the city of santri because there are many Islamic boardingschools which are famous in Indonesia domiciled in this city. At least there are seven large Islamic boardingschools located in the Jombang area. Apart from the strategic geographical location in the city of santri,great figures were born, one of which was the forerunner of the resistance of the community and the santritowards the invaders who were commanded by Hadratussyaikh KH.M Hasyim Asy'ari, the founder ofNahdlotul Ulama and KH. A Wahid Hasyim, 4th President K.H Abdurrahman Wahid. Based on thedescription above, in order to help parents who want to know the geographical location and the teachingsystem in Islamic boarding schools in Jombang, the application of mapping boarding schools is neededwhich can help parents know what kind of boarding school information is in Jombang Regency with 3groups, namely: Salaf Islamic Boarding School, Traditional Islamic Boarding School and Tahfidz IslamicBoarding School and know the geographical location of Islamic boarding schools with website-basedmapping visualization.Keywords: Jombang Regency, Islamic Boarding School, Mapping